EFFECTS OF IMMUNIZING PREGNANT EWES AND DOES ON THE HUMORAL IMMUNE RESPONSE OF SECRETED COLOSTRUM (Journal of Animal and Plant Sciences, 2018)
The main objective of the study was to produce hyperimmune colostrum of ewes and does by vaccinating them during their pregnancy and to examine the performance of their lambs/ kids receiving the colostrum from the dams. Animals were divided as control (T-1) without vaccination and 3 treatments (vaccinated flocks) (T2-T4). The vaccines used were; Clostridia sp., Pasteurella sp., and Sheep pox. Study variables were concentration of immunoglobulins (Igs) in both serums’ of ewes/ does as well as quantifying the Ig classes of colostrum of both species. Results showed that vaccination of pregnant ewes and does were improved by doubling of serum’ Igs in vaccinated dams compared to the control flock. Likewise, a significant increase of colostrum’ Igs of ewes and does by 20 and 23%, while serums’ Igs of the dams increased by 48 % of both species. The studies focused on challenging pregnant dams with individual vaccines of Clostridia sp., Pasteurella sp., and Sheep pox. Morbidity and mortality rates during the early age of offspring were almost none in vaccinated flocks compared to those without vaccination.
Keywords: Hyperimmune colostrum; immunoglobulin; vaccination; mortality; lambs; kids